Bioactive Compounds Extraction Using a Hybrid Ultrasound and High-Pressure Technology for Sustainable Farming Systems - Florin Nenciu; Viorel Fatu; Vlad Arsenoaia; Catalin Persu; Iulian Voicea; Nicolae-Valentin Vladut; Mihai Gabriel Matache; Iuliana Gageanu; Eugen Marin; Sorin-Stefan Biris; Nicoleta Ungureanu (Agriculture, 2023)
In the context of agricultural soil degradation caused by the extensive use of chemical amendments, ecological alternatives with minimal detrimental impact on ecosystems are gaining popularity. Recent advancements in processing technologies have improved the quality and extraction efficiency of bioactive compounds, particularly when multiple conventional or innovative techniques are being used to potentially overcome the most common limitations. This paper proposes the development and testing of a hybrid technology design that employs two extraction techniques, namely ultrasound and high pressure, that can be used either separately or in tandem. An initial assessment of the prototype potential for isolating the desired compounds was made, by testing three various working regimens for the processing of a mixture of onion, pea, and soybean. By incorporating the bioactive compounds produced during the experimental phase in the seedling transplantation holes, we were able to test the potential of stimulating the development rate of vegetables and reducing the attack of pests. The extracts obtained using the hybrid technology showed positive results when used to reduce pest attacks (decreasing average attack frequency by 7%), however had negative effects when used to promote biostimulation, when acted as an inhibitor. The hybrid extraction approach improved the mass transfer into solvent by 14% when compared to high-pressure processing and by 7% when compared to sonication.